On the platinum-oxide formation under gas-phase and electrochemical conditions - Farkas, Attila; Fantauzzi, Donato; Mueller, Jonathan E.; Zhu, Tianwei; Papp, Christian; Steinrück, Hans-Peter; Jacob, Timo (Journal of Electron Spectroscopy and Related Phenomena, 2017)
We summarize our recent results on the oxidation of platinum surfaces, stressing the close connection between theory and experiment. The present theoretical approach is based on ab-initio quantum mechanics methods, such as density functional theory (DFT), ab-initio atomistic thermodynamics, Monte-Carlo methods and reactive molecular dynamics (RMD). Experimentally, photoelectron spectroscopy (XPS) under UHV and in-situ conditions (NAP-XPS) provides most of the discussed results. The oxidation of an extended variety of platinum surfaces is reviewed, starting from atomically flat Pt(111) over stepped surfaces to regularly shaped nanoparticles, under conditions ranging from UHV through ambient pressures up to electrochemical interfaces.
EAM Import::2019-03-08